1977
DOI: 10.1149/1.2133143
|View full text |Cite
|
Sign up to set email alerts
|

Formation of Thick Layers of Iodine During the Anodic Oxidation of Iodide on a RDE: II . Open‐Circuit Behavior

Abstract: The open‐circuit behavior of iodine layers formed on a RDE during the anodic oxidation of iodide was investigated. A plateau in potential was observed. Its value was found to depend on the concentration of free iodine in solution, and its length on the amount of iodine on the surface. It was shown that the sudden change in the nature of the iodine layer associated with the sharp decrease in current is not due to a phase transformation from super‐cooled liquid to solid iodine. The rate of decay of potential on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…The formation of I 2 -film layers during the electro-oxidation of I – has been reported in several previous studies. To quantitatively analyze the amount of the I 2 -film, the mass change of the graphite/quartz composite electrode during a CV test was monitored using eQCM (Figure a). The resonance resistance showed a constant value with a random fluctuation, suggesting its little effect on the resonance frequency (Figure S1).…”
Section: Results and Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…The formation of I 2 -film layers during the electro-oxidation of I – has been reported in several previous studies. To quantitatively analyze the amount of the I 2 -film, the mass change of the graphite/quartz composite electrode during a CV test was monitored using eQCM (Figure a). The resonance resistance showed a constant value with a random fluctuation, suggesting its little effect on the resonance frequency (Figure S1).…”
Section: Results and Discussionmentioning
confidence: 79%
“…The second decrease is ascribed to the formation of the I 2 -film on the electrode surface, preventing the charge-transfer reaction and/or mass transfer of I – ions from the bulk solution to the electrode surface. Most previous studies focused only on the reduction of the mass-transfer rate of I – ions. They attributed the sudden drop of the current to an increase in the specific resistance of the I 2 -film because the film impedes the diffusion of I – ions. Here, we investigate the change in the charge-transfer resistance ( R ct ) at the electrolyte/electrode interface during the development of the I 2 -film.…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that aqueous iodide undergoes spontaneous oxidation upon chemisorption to form a layer of zerovalent atomic iodine on platinum electrodes at potentials between 0 and +0.4 V vs SCE 30,31. Under higher potentials, molecular iodine would be formed due to further deposition of atomic iodine, which can either lead to the formation of solid iodine 32,33 or dissolution into the solution phase. At higher concentrations of iodide (greater than ca.…”
Section: Resultsmentioning
confidence: 99%